THE COMBINATION OF FISH MEAL, SOYBEAN MEALS AND DEHULLED LUPIN IN FISH FEED AND THEIR EFFECTS ON THE GROWTH OF RED TILAPIA (Oreochromis niloticus) - J.H. Hutabarat (JOURNAL OF COASTAL DEVELOPMENT, 1999)
The amis of the study were to determine the combination of fish meal, soybean meals, and dehulled lupin meal in fish feed and their effects on the growth and survival rate of Oreochromis niloticus. There treatments at different substitution levels of lupin dehulled meals to the soybean meals as main source of plant protein i.e 50% of soybean meals+ 50% fish meals (A), 50% Fm + 25% SB + 25% Lm (B) and 25% FM + 25% SB + 25% LM (C) were adopted in this study. The red tilapia (Oreochromis niloticus) with initial weight ranging from 238,67 – 239,65 g/fish with stocking density of 150 fish per cage were used as experimental fish. The study was conducted in Rawa pening Lake, Ambarawa – Central Java, from December 1998 to March 1999. The results indicated that different combination of duhulled lupin and soybean as plant protein source in fish feed had significantly affected (P<0,05) the absolute growth and NPU, and hat not significantly affected the daily growth rate, FCR, SR, and PER. The best absolute growth (292,05g), daily growth rate (1,34%/day), FCR (2,31), PER (1,68) and NPU (8,37), were achieved by treatment B, followed by C and A. meanwhile, the best SR was achieved by treatment C and followed A, and B. Therefore, treatment B appeared to be the best fish feed formulation for Red tilapia production.